Evidence of Major Structural Features over the Pan-African Domain in the Bertoua-Mbangue Area (East Cameroon) from a Multiscale Approach of Modeling and Interpretation of Aeromagnetic Data - Owono Amougou Olivier Ulrich Igor; Ndougsa Mbarga Theophile; Meying Arsène; Assembe Stephane Patrick; Ngoh Jean Daniel; Ngoumou Paul Claude; Yandjimain Justine (International Journal of Geophysics)
The aim of this study is to investigate crustal structures from East Cameroon, using aeromagnetic data. The modeling of aeromagnetic data is conducted using the Oasis Montaj 8.0 software. The total magnetic intensity map reduced to the equator (RTE-TMI) shows important anomalies features, namely, the Northern East magnetic anomalies of high amplitude, the Southwest where very low values of the magnetic intensity were observed, and a corridor with negative values relatively high, separating the anomalies. The horizontal gradient map shows on the one hand brittle and folded structures carried out in the area of study and on the other hand various rectilinear, narrow, and short-wave anomalies that can be classified as a family of little faults. The maxima observed on the RTE-TMI maps are correlated to intrabasement contacts; and the map derived from Euler’s solutions permitted to evaluate the depth of the geological accidents observed from the other filters. This map also reveals new faults with a depth greater than 5000 m. The lineaments identified in the Southwestern part could be linked to the Pan-African orogeny and seem to correspond to deep-seated basement structures, which are referred to the tectonic boundary between Congo Craton and the Pan-African orogeny belt. A 23/4-D modeling confirmed the observations derived from the RTE-TMI and HGM maps analyses. It shows intrusive bodies composed of gneiss and porphyroid granite and some domes with their roof situated at various depths not exceeding 1800 m from the surface. The structural map of the study area shows the trending of the structural features observed, namely, NE-SW, NW-SE, ENE-WSW, and WNW-ESE, respectively, while the E-W and N-S are secondary orientation of the observed tectonic evidence. Moreover, circular anomalies observed over the area are assimilated to intrusions of high magnetic materials or to granitic domes.